2007
DOI: 10.1074/jbc.m608985200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase A-dependent Translocation of Hsp90α Impairs Endothelial Nitric-oxide Synthase Activity in High Glucose and Diabetes

Abstract: Diabetes mellitus (DM) and high glucose (HG) are known to reduce the bioavailability of nitric oxide (NO) by modulating endothelial nitric-oxide synthase (eNOS) activity. eNOS is regulated by several mechanisms including its interaction with heat shock protein (Hsp) 90. We previously discovered that DM in vivo and HG in vitro induced the translocation of Hsp90␣ to the outside of aortic endothelial cells. In this report we tested the hypothesis that translocation of Hsp90␣ is responsible for the decline in NO p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 57 publications
7
66
0
Order By: Relevance
“…Moreover, a series of Akt binding partners were reported to modulate its phosphorylation and activity; whereas JIP-1 (70), Ft-1 (71), and TCL-1 (72) can directly modulate Akt activity, others, like Hsp90, act indirectly by protecting it from the action of inactivating phosphatases (73). Interestingly, Hsp90 was recently identified as a PKA substrate, and its phosphorylation negatively affects its ability to associate with endothelial nitric-oxide synthase (74). Whether an analogous PKA-dependent effect on Hsp90/Akt accounts for the inhibitory action of cAMP is for the moment unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a series of Akt binding partners were reported to modulate its phosphorylation and activity; whereas JIP-1 (70), Ft-1 (71), and TCL-1 (72) can directly modulate Akt activity, others, like Hsp90, act indirectly by protecting it from the action of inactivating phosphatases (73). Interestingly, Hsp90 was recently identified as a PKA substrate, and its phosphorylation negatively affects its ability to associate with endothelial nitric-oxide synthase (74). Whether an analogous PKA-dependent effect on Hsp90/Akt accounts for the inhibitory action of cAMP is for the moment unknown.…”
Section: Discussionmentioning
confidence: 99%
“…36,37,40,41 Further, PKA phosphorylation of Thr90 induced by 3-hydroxy-3-methylglutarylcoenzyme A reductase inhibitors has been reported to increase association of human Hsp90α with the client protein eNOS. 42 Lastly, a study reported that protein phosphatase 5 (Pp5/Ppt1) can dephosphorylate Hsp90 in vitro. 43 This study also showed that Ppt1 deletion in yeast compromised Hsp90 activity.…”
Section: Tyrosine Phosphorylation Of Hsp90mentioning
confidence: 99%
“…In addition to cochaperone association as well as ATP binding and hydrolysis, posttranslational modifications such as hyperphosphorylation (13)(14)(15), S-nitrosylation, and reversible hyperacetylation have also been shown to regulate the chaperone function of hsp90 (16)(17)(18). Several serine-threonine phosphorylation sites have been identified in hsp90.…”
Section: Introductionmentioning
confidence: 99%